Contradictory totality in two disputed genres: the fox from above and the fox from below by José María Arguedas - Rivas Sucari, Henry César (2021)
This paper aims to address the tensions observed in the novel El zorro de arriba y el zorro de abajo (The Fox from Above and the Fox from Below)by José María Arguedas. The study is interested in the proposal of "testimonial novel -intimate diary" from the metaliterature, and its relation with the "social novel" represented by the conflict of the fishermen in Chimbote in the novel. The category of contradictory totality elaborated by Antonio Cornejo Polar will be useful to inquire about the precision of the novel's genre. It is assumed that it obeys a balanced structuring from genres in conflict, but which can be read as a unit. On the other hand, the contributions of Hans Rudolf Picard and Camarero will be useful to examine the relationship between the Novel-Diary genre and Literature.